BACK MUSCLES STRENGTH DEVELOPMENT BY MEANS OF INCREASE AND DECREASE OF EFFORT LOAD DURING GIANT SETS IN BODYBUILDING FOR MASSES - TIMNEA OLIVIA; POTOP VLADIMIR; ULĂREANU MARIUS (Ovidius University Press, 2013)
Abstract The aim of the study is to highlight methodological issues on the back muscle strength development by combining methodological procedures in masses bodybuilding.Methods. The study was conducted in three stages over a period of two months (March-April 2011), performing three workouts per week, monitoring the effective use of strength exercises to develop back muscles in the same muscle area by means of giant sets during workouts. In this context, we conducted a case study in "Tonik Fitness Club" in Bucharest, applied to two athletes of 28 and 34 years old. We recorded subjects' evolutions during the training session, using statistical and mathematical method and graphical representation method.Results. The study content highlights the training programs depending on muscle zone and the specific methodological aspects, the weekly training program per muscle groups, the stages of study carrying out, the test and control trials applied in terms of anthropometric measurements and of back muscle strength development, and the application of the methodical procedure of effort load increase and decrease within the giant sets in a training micro-cycle.Discussion. The study focused on the training programs over two months, monitoring statistically the development of back muscle strength through the application of the procedure of effort load increase and decrease during giant sets in bodybuilding for masses. From the analysis of training programs content we noticed that three giant sets of exercises were used, performed in four series; each exercise within the giant sets was applied by means of the procedure of increasing and decreasing effort load. Study results emphasize the anthropometric measurement results: the study subjects have the age mean of 24.75, with a size of 175.2 cm and a weight of 83.75 kg at initial testing and a decrease by 2.12 kg in final testing. Regarding the chest perimeter, the inspiration is averaging 89.5 in initial testing and an increase of 2.25 cm in final testing; the expiration is averaging 85.25 cm in initial testing and an increase of 1.75 cm in final testing, while the amplitude has an average of 4.25 cm at initial testing and an increase of 1.0 cm at final testing. As for arms perimeter, at the initial testing of the right arm they had an average of 38.25 cm and 0.65 cm increase in final testing, the left arm - an average of 38.88 cm at initial testing and an increase by 0.12 cm in final testing. From the analysis of back muscle strength, it was noticed an increase by 4.5 reps in "pull-downs" final testing, an increase by 16kg of the load in " cable machine chest pull-downs ", with an average of 84kg at initial testing and 100 kg in final testing, performed with 13 reps at initial testing and a decrease by 4 reps in final testing. In "seated rowing at machine" there is an increase of the average by 16 kg of load, with an average of 92kg at initial testing and an average of 108kg in final testing, with 11 reps performed in initial testing and a decrease by 2 reps in final testing.Conclusions. The study results show that the regular exercising leads to a decrease of body weight, an increase of thoracic amplitude, of arms perimeters and last, but not least, to strength development per different muscle groups.The study highlights methodological issues on the back muscles strength development by combining methodological procedures in bodybuilding for masses, by increasing and decreasing effort load during giant sets. And the effective use of strength exercises for back on the same muscle area by means of giant sets during a training session helps to improve muscle endurance and to increase strength at different machines. Also the division of back muscles areas during each training micro-cycle emphasizes the dynamics of muscle strength and the possibility to combine muscle groups together during a training mezzo-cycle.